2021
DOI: 10.1016/j.ygyno.2021.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Low preoperative skeletal muscle density is predictive for negative postoperative outcomes in older women with ovarian cancer

Abstract: Low preoperative skeletal muscle density measured on an abdominal CT scan is associated with worse postoperative outcomes.• Preoperative low skeletal muscle mass is associated with infectious complications, but not with other outcomes.• Preoperative low skeletal muscle density is of added value to functional impairment in predicting surgical complications.• Low skeletal muscle quality and functional impairment can be seen as markers for sarcopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This result is interesting because SMD represents the fatty infiltration of muscle (with higher values corresponding to lower fat infiltration of the muscle fibers), which is considered an indirect estimate of muscle quality. Furthermore, other studies have also demonstrated that SMD is associated with prognosis [51][52][53][54].…”
Section: Discussionmentioning
confidence: 92%
“…This result is interesting because SMD represents the fatty infiltration of muscle (with higher values corresponding to lower fat infiltration of the muscle fibers), which is considered an indirect estimate of muscle quality. Furthermore, other studies have also demonstrated that SMD is associated with prognosis [51][52][53][54].…”
Section: Discussionmentioning
confidence: 92%
“…From the three electronic databases and references of related studies, we identifed 1,979 studies. After reviewing the title, abstract, and full text, nine studies [13][14][15][16][24][25][26][27][28] were fnally included in this systematic review and meta-analysis (Figure 1). Te median NOS quality score was 8 (range from 6 to 8) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there have been reports not only on the volume and the area of skeletal muscle but also on the skeletal muscle density, with individuals having low skeletal muscle density often referred to as having myosteatosis [36][37][38][39][40]. Moreover, muscle density can also be measured using CT, similar to PA and PV.…”
Section: Discussionmentioning
confidence: 99%